A study of gender preference, knowledge and attitude regarding prenatal diagnostic techniques act among pregnant women in an urban slum of Bengaluru - B., Pavithra M.; Dhanpal, Sudeepa; Lokanath, Hamsa (International Journal Of Community Medicine And Public Health, 2017)
Background: Preference for a son continues to be a prevalent norm even in modern India which is evident from the recent census report. The most alarming aspect is a further fall in child sex ratio (0-6 years) from 927 in 2001 to 914 in 2011. Sex selective abortion is the major factor responsible for this unfavorable trend. The objective was to assess the knowledge, attitude and practice of pregnant women regarding Prenatal Diagnostic Techniques (PNDT) Act and gender preference. Methods:A cross-sectional study was carried out in100 pregnant women attending the antenatal clinics of Sulthanpalaya Urban health center, Bangalore. A pre-designed and pre-tested questionnaire was used to get information. Data was analyzed by using Statistical Package of Social Sciences (SPSS) 16.0. Results: In this study 53% showed preference for a male child. Only 37% were aware about the decline in sex ratio and 59% knew that PNDT act existed and sex determination was legally wrong. Over all 41% had poor knowledge. Whereas 43% had average and 16% had good knowledge and 74% had the right attitude in this study. Good knowledge about PNDT act had significant influence on the attitude of the people (p< 0.05). Conclusion: The falling ratio of girl child is a matter of grave concern. Effective implementation of the PNDT Act in addition to spreading awareness about this act among people is the need of the hour. Moreover, it is necessary to gear efforts against the cultural, economic and religious roots of this social malady by woman empowerment.